The efficacy and safety of the open approach irreversible electroporation in the treatment of pancreatic cancer: A systematic review. Issue 9 (September 2020) - Charalambous, Pabos; Moris, Dimitrios; Karachaliou, Georgia-Sofia; Papalampros, Alexandros; Dimitrokallis, Nikolaos; Tsilimigras, Diamantis I.; Oikonomou, Dimitrios; Petrou, Athanasios
Abstract: Background: Irreversible Electroporation (IRE) is a novel non-thermal ablation technique used in patients with locally advanced pancreatic cancer (LAPC), in the proximity of sensitive structures such as vessels, intestinal wall and the bile duct. Currently, it is only used in the setting of clinical trials. This systematic review aimed to tackle the knowledge gap in the literature, in relation to the safety and efficacy of the open approach IRE. Methods: MEDLINE, EMBASE and Cochrane libraries were searched for English language articles published from January 2000 to December 2019. Data related to safety and efficacy were extracted. Results: Nine studies involving 460 patients with LAPC were included. Open approach IRE was associated with high morbidity (29.4%) but with a survival benefit compared to traditional treatment. Median overall survival (OS) was at 17.15 months. Major morbidity was at 10.2% and mortality at 3.4%. Conclusions: Despite the paucity of literature and the low quality of evidence, the results regarding safety and efficacy appear to be encouraging. The high morbidity seems to be mitigated by a demonstrated improvement in OS. The potential of this technique is more evident when mortality and major morbidity are considered, since they are at acceptable levels. The limitations of this review have made it difficult to extract definitive conclusions. Higher quality evidence is needed in the form of large-scale multicentre randomized controlled trials. It remains to be elucidated whether the rate of adverse events decreases as our experience with this technique increases.